Investigating food web structure and system function of an artificial reef ecosystem based on carbon and nitrogen stable isotope analysis: implications for reef management - Jie Feng; Xiaolong Zhao; Fan Bi; Wei Zhao; Liang Zhao; Hao Song; Meijie Yang; Zhi Hu; Cong Zhou; Pu Shi; Pengpeng Hu; Peizhen Ma; et al. (Frontiers in Marine Science, 2023)
Introduction Food web is an important basis for identifying trophodynamic processes, and evaluating the structural and functional characteristics of ecosystems. The trophodynamics and system function of artificial reef (AR) ecosystems have rarely been examined. Methods Stable isotope analysis was used to investigate the food web structure and functions of an artificial reef (AR) ecosystem in this study. Results and Discussion The δ13C and δ15N values of particulate organic matter (POM) in AR showed noticeable seasonal changes, and the δ13C value of POM in autumn was significantly higher than that in other seasons (p<0.05). There were no significant seasonal variations in the δ13C values of solid organic matter (SOM), and no significant difference between SOM and POM was observed except in autumn. Moreover, macroalgae did not significantly affect the δ13C values of SOM. Phytoplankton may be the primary nutrient source in the AR ecosystem. The δ13C values of most crustaceans in the AR were approximately between (-17.03 ± 0.22) ‰ – (-17.74 ± 0.07) ‰, higher than those of most fish, indicating that they may have different basal nutrient sources. The trophic level (TL) of invertebrates was between 2.00 and 3.09, and that of fish was between 2.98 and 3.66. The distribution of δ13C and TLs of crustaceans and fish showed that, except for crustaceans, bivalve shellfish and zooplankton might also be important food sources for fish in the AR ecosystem. Conclusion The δ13C and δ15N values of most species in the AR showed good continuity, indicating that they may be mainly produced from the AR ecosystem. Migratory species such as Lateolabrax japonicus and Sepiella maindroni showed higher δ13C values, indicating that they may have migrated from other sea areas. To maintain the stability of the ecosystem structure and function of the AR ecosystem, fishing activities should be carried out following the maximum sustainable yield theory. Future research needs to identify the nutritional relationship between AR and its adjacent sea areas, to depict the food web structure of the AR with higher accuracy.